On art - Kabakov, Ilʹja Iosifovič 1933-2023 (The University of Chicago Press, 2018)
"This volume offers for the first time in English the most significant texts written by the Russian conceptual artist, performer, and painter Ilya Kabakov. The writings have been expressly selected for this English-language volume; there exists no equivalent volume in any language."...Provided by publisher
Includes bibliographical references and index
Keywords: Art; Art, Russian; Art, Modern -- 20th century; Installations (Art); Conceptualism; Art -- Philosophy; Concept-art; Kunst; Russland